Prevalence and factors associated with mild cognitive impairment on screening in older Malaysians - Kamarolzaman, Khairiah; Ching, Siew Mooi; Tengku Abdul Hamid, Tengku Aizan (Yerkure Tanitim ve Yayincilik Hizmetleri A.S., 2016)
Objective: This study was aimed to determine the prevalence and predictors of mild cognitive impairments (MCIs) in Malaysia. Method: This is a cross-sectional community-based study among elderlies aged 60 years and above in the four states of Malaysia - Perak, Kelantan, Selangor and Johor. A multi-stage stratified random sampling method was used for the data collection. Mini Mental State Examination score ?22 was used to diagnosed MCI and analyzed by using multivariate logistic regression. Results: A total of 2112 participants were recruited into this study. Mean age of the participants was 69.2±18.8 years, and 51.4% of them were females. The ethnic distribution was 63.4% Malaysian, 31.4% Chinese, 5.0% Indians, and 0.2% others. The overall prevalence of MCI was 68% (n=1436/2112). In multivariate logistic regression analysis, participant who were older (OR 1.02, 95% CI 1.00-1.04), did not receive formal education (OR 6.85, 95% CI 4.58-10.25), had primary education (OR 2.35 95% CI 1.84-3.00), were lonely (OR 1.18 95% CI 1.05-1.32), and had low level of life satisfaction (OR 1.68 95% CI 1.02-2.67), had significant positive correlations with MCI. Conclusion: MCI is present in seven out of ten elderly Malaysians. Aging population, presence of low education level, loneliness and low life satisfaction level seem to facilitate development of MCI.